(untitled) (Foro de Educacion, 2023)
In order to ascertain the recent development of Intercultural Education in Latin America, this study undertakes a review of research on this topic over the 2010-2019 decade. It is a research on the state of the art, for which the results published in the most important Latin American scientific journals in the field of education were selected, indexed in SCOPUS or JCR. The sample consists of 20 journals and 70 articles. After circumscribing the concept of Intercultural Education, the selected journals are briefly analysed and grouped together (by topic, characteristics, methodology and research techniques used, interventions carried out, etc.), submitting the whole group to due statistical analysis. Among the main findings, we should point out three main ideas as agents of change in the research carried out, that is, the response to cultural diversity in schools, teacher training and the indigenous differential, approached basically from a qualitative methodology. At the same time, we identify points which are likely to receive increased attention in this field of study. Finally, we make some suggestions and recommendations for future research on this topic, based on the evidence provided, as well as on the complexity associated with the ever-growing level of uncertainty in the social environments.